AB0156 Expression of autophagy "markers" in monocytes from patients with active early rheumatoid arthritis. (23rd January 2014) - Iannuccelli, C.; Misasi, R.; Di Franco, M.; Alessandri, C.; Capozzi, A.; Lococo, E.; Olivieri, M.; Sorice, M.; Valesini, G.
Abstract : Background: Autophagy is a fundamental self-degradative process in eukaryotic cells via the lysosomal pathway, involved both in basal turnover of cellular components and in the response to nutrient starvation (1). The immune system utilizes autophagy to restrict intracellular pathogens and regulate adaptive immunity, thus autophagy, as well as apoptosis, could be relevant in induction or loss of self tolerance to intracellular molecules and might act as a source of autoantigens in autoimmune diseases (2). Objectives: Aim of our study was to study the monocyte autophagy in patients with active early RA naïve to steroids and DMARDs before and after 3 months of therapy. Methods: 17 early RA patients (mean age 49 yrs, mean disease duration 21 weeks), fulfilling both 1987 and 2010 ACR criteria, naïve to treatment, were recruited after written informed consent. Before (T0) and after 3 months of treatment (T1), DAS28 was calculated, CRP was assessed. Autophagy markers (LC3, Ambra, beclin) were evaluated by flow cytometry on isolated monocytes. As a control group, 10 healthy donors were also evaluated. Results: As expected, CRP, GH and DAS 28 score were significantly reduced following treatment with steroids and DMARDs (Table 1 ). Autophagy markers (LC3, Ambra, beclin) showed a similar behaviour, reducing their expression in monocytes after treatment (Tab.1). Interestingly, the expression of autophagy markers was significantly related to DAS28 (p=0.04 for LC3, p=0.03 for Ambra), to GH (p=0.01 for Ambra), and to CRP (p=0.01 for Ambra, p=0.006 for beclin). Conclusions: These data indicate an increased expression of autophagy markers in isolated monocytes from patients with active early RA, suggesting a possible role for autophagy in the pathogenesis of this disease. The relationship between autophagy and acute inflammation is supported by the significant reduction of autophagy markers after therapy, together with their relationship with DAS28, GH, and CRP. Our results may contribute to clarify whether endogenous or pharmacological regulation of autophagy might modify the autoimmune response and the progression of the disease. References: Lleo A et Al, J.Autoimmun 2007;29:61-68. Deretic V, Curr Opin Immunol 2009;21:53-62. Disclosure of Interest: None Declared